1994
DOI: 10.1159/000282642
|View full text |Cite
|
Sign up to set email alerts
|

In situ Extracorporeal Shockwave Lithotripsy of Distal Ureteral Stones: Parameters for Therapeutic Success

Abstract: Between January and December 1989, 123 patients with distal ureteral stones were treated with in situ extracorporeal Shockwave lithotripsy (ESWL) using a modified HM3 Dornier lithotriptor. One hundred and three patients (83.7%) were stone-free, 20 patients (16.3%) had small residual stones ( < 1 mm2) that passed spontaneously. In situ ESWL treatment alone was successful in 88 of the 103 stone-free patients (85.4%). Fifty-six (54.4%) needed 1 ESWL session, 26 (25.2%) needed 2 ESWL sessions. Nineteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…Chaussy and colleauges 13 suggested that a stone was less likely to break if its density was greater than that of vertebral spine on a plain abdominal film. Mattelaer and colleauges 14 concluded that highly opaque stones were less fragile with ESWL therapy. Others have shown that smooth, uniform stones that appeared denser than bone (12th rib) on a plain abdominal film responded poorly to ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Chaussy and colleauges 13 suggested that a stone was less likely to break if its density was greater than that of vertebral spine on a plain abdominal film. Mattelaer and colleauges 14 concluded that highly opaque stones were less fragile with ESWL therapy. Others have shown that smooth, uniform stones that appeared denser than bone (12th rib) on a plain abdominal film responded poorly to ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this latter study [22] the post-ESW L secondary endoscopic proce dure rate including ureteral stents for ureteral stones was only about 5% whereas in other studies [5,20,21] up to about 15% o f the patients need auxiliary endourological procedures to completely disintegrate or extract the stone fragments. Mattelaer et al [5] considered the parameters size o f the ureteral stone, radiopacity, and grade of obstruction as prerequisite to predict the outcome o f pri mary in situ ESW L o f distal ureteral calculi. In our study only 34 o f 639 patients (5.3%) with stones in the distal ureter treated primarily by ESW L required ureteroscopy as an auxiliary measure, and 29 (85%) o f them were ren dered free o f their stones using this endoscopic procedure.…”
Section: Discussionmentioning
confidence: 63%
“…As many as 20% o f the patients treated by in situ E SW L for distal calculi require either repeated ESW L or an auxiliary procedure after ESW L [5,16,19], The relatively high ESW L retreatment rate in the present study (18.9%), similar to that o f other authors [20,21 ], seems to be the price for the higher success rate com pared to the study o f Cass [22]. Furthermore, in this latter study [22] the post-ESW L secondary endoscopic proce dure rate including ureteral stents for ureteral stones was only about 5% whereas in other studies [5,20,21] up to about 15% o f the patients need auxiliary endourological procedures to completely disintegrate or extract the stone fragments. Mattelaer et al [5] considered the parameters size o f the ureteral stone, radiopacity, and grade of obstruction as prerequisite to predict the outcome o f pri mary in situ ESW L o f distal ureteral calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Bu ko nu da ilk ola rak kon van siyo nel direkt gra fi de ta şın rad yo dan si te si ver teb radan az ise kı rı la bi le ce ği, ancak di rekt gra fi ler de rad yo dan si te si faz la taş la rın ay nı bo yut ta ki taş la ra gö re 1.7 kat da ha faz la şok sa yı sı ge rek tir di ği ni ancak de ğer len dir me nin süb jek tif ol du ğu be lirt ilmiş -tir. [14][15][16] Kon trast sız BT'nin üri ner sis tem taş la rın da kul la nı mı nın po pü ler ol ma sıy la be ra ber taş kompo zis yo nun ön ce den tes pi tin de to mog ra fi den yarar la nı lan ça lış ma lar ya pıl ma ya baş lan mış ve fark lı taş kom po zis yon la rı nın BT yo ğun luk de ğer le ri rapor edi le rek, kon trast sız BT taş yo ğun luk de ğer leri nin, süb jek tif olan kon van si yo nel direkt grafi taş dan si te sin den da ha iyi ay rım sağ la dı ğı be lir til miş -tir. [6][7][8][9][10] Ba zı otör le re gö re ise ko nu ile il gi li ra por ların tar tış ma lı ol du ğu ve ba zı taş kom po zis yonla rı nın yo ğun luk de ğer le rin de ça kış ma iz len me si ne de niy le sa de ce kal si yum taş la rı nın ürik asit taş-la rın dan ay rı la bi le ce ği ifa de edil mek te dir.…”
Section: Tar Tiş Maunclassified
“…[6][7][8][9][10][11][12][13] Kon van si yo nel direkt gra fi rad yo dan si te le ri nin, kı-rı la bi lir li ği be lir le me de et ki si ni de ğer len di ren az sa yı da ça lış ma ise süb jek tif göz lem le re da yan dı ğın -dan bağ la yı cı ne ti ce ler ve re me mek te dir. [14][15][16] Bu ça lış ma ile üri ner sis tem taş la rı nın kon vansi yo nel direkt grafi rad yo dan si te sin den el de edi len gri ska la de ğer le ri nin ESWL te da vi sin den ön ce taşın kı rı la bi lir li ği ni ön gö re bil me et kin lik le ri nin değer len di ril me si amaç lan mış tır.…”
unclassified